Adiponectin: A potential candidate for treating fibrosis in posterior segment of the eye. (February 2019) - Palanisamy, Karthikka; Raman, Rajiv; Sulochana, Konerirajapuram Natarajan; Chidambaram, Subbulakshmi
Abstract: Fibrosis in ocular tissues causes severe visual deterioration and blindness in patients with glaucoma, cataract, age related macular degeneration (AMD) and diabetic retinopathy (DR). Currently available anti-fibrotic agents exhibit undesirous cytotoxic effects and thus prove ineffective to treat post-surgical fibrosis. Accordingly, there is a need to develop efficient and novel anti-fibrotic agents. Adiponectin (APN), an adipokine from adipocytes is increased in the aqueous and vitreous humor of the patients with micro-angiopathy and chronic inflammation. Furthermore, it is reported to be elevated in the subretinal fluid, vitreous and epiretinal membrane of patients with AMD, proliferative vitreoretinopathy (PVR) and proliferative diabetic retinopathy (PDR) respectively. Since APN has anti-angiogenic activity and reduces VEGF levels, we hypothesize that APN might regulate the angio-fibrotic switch and drive the formation of fibrovascular membrane at advanced stages of AMD, PVR and PDR. Intriguingly, APN is shown to inhibit liver, cardiac and pulmonary fibrosis, yet it accelerates renal fibrosis. Therefore, the factors such as tissue and cell type, disease specific pathological milieu and the choice of APN receptor interaction could determine the pro- or anti-fibrotic nature of APN. We speculate that APN could play a profibrotic role in the posterior segment of the eye.